2021
DOI: 10.2298/abs210111004s
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin postconditioning combined with sitagliptin exerts full cardioprotection in diabetic hearts of aged rats through an AMPK-dependent mechanism

Abstract: The presence of multiple comorbidities in patients facing myocardial ischemia-reperfusion (IR) injury is the main obstacle for cardioprotection. This study investigated the effect of melatonin postconditioning combined with sitagliptin pretreatment on cardioprotection in diabetic aged rats by evaluating oxidative stress, apoptosis and involvement of the AMPK/SIRT1 pathway. The type-2 highfat/ streptozotocin experimental model in aged Sprague-Dawley rats (n=78) was used. The animals underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… Male Sprague Dawley rats 22 ± 2 (months) 300–325 (g) T2DM T2DM (a high-fat diet (62% calories obtained from fat)/ diet + 35 mg/kg of STZ by intraperitoneal + Melatonin (10 mg/kg) + Sitagliptin (20 mg/kg, i.p.) for 4 weeks N = 42 7 groups (6 rats each) 1—control group received only thoracotomy without LAD ligation; 2—IR groups; 3—IR + Melatonin group; 4—IR + Sitagliptin group; 5—IR + Melatonin + Sitagliptin group; 6—IR + CC group; 7—IR + CC + Melatonin + Sitagliptin group 2 weeks 10 weeks Improving antioxidative and antiapoptotic responses Up-regulation of AMPK/SIRT1 activity via melatonin [ 100 ] Male C57BL/6 J mice 8 weeks T1DM T1DM 50 mg/kg (STZ) by intraperitoneal for 5 consecutive days + intraperitoneal injections of 10 mg/kg/d melatonin for 10 weeks 4 groups 1—normal glucose; 2—high glucose; 3—Mannitol; 4—melatonin 2 weeks 12 weeks after the first injection of STZ amelioration of high glucose-induced CMECs injury by melatonin Treatment of apoptosis and increased AMPK/SIRT1 signaling axis activity by melatonin in CMEC [ 101 ] Adult male Wister rats 8 weeks 170–200 (g) T2DM T2DM nicotinamide (100 mg/kg, ip) 20 min before STZ (55 mg/kg) + melatonin (10 mg/kg) by stomach tube daily for 15 days between 10:0 and 11:00 am N = 20 4 groups (5 rats each) 1—control group received standard diet 2—melatonin treated group 3—diabetic group 4—group receiving melatonin for 15 days after the induction of diabetes 3 days 15 days post diabetic induction of STZ Protective effects of melatonin against hyperglycemia, anti-lipid, antioxidant, anti-inflammatory and anti-apoptotic MLT improves serum glucose levels, HbA1-c, lipid profile, insulin levels and insulin resistance, glutathione and IL-10 and Bcl-2 levels and prevents the increase of pro-inflammatory cytokines and the expression of Bax, caspase-3 and P53 [ 9 ] …”
Section: Resultsmentioning
confidence: 99%
“… Male Sprague Dawley rats 22 ± 2 (months) 300–325 (g) T2DM T2DM (a high-fat diet (62% calories obtained from fat)/ diet + 35 mg/kg of STZ by intraperitoneal + Melatonin (10 mg/kg) + Sitagliptin (20 mg/kg, i.p.) for 4 weeks N = 42 7 groups (6 rats each) 1—control group received only thoracotomy without LAD ligation; 2—IR groups; 3—IR + Melatonin group; 4—IR + Sitagliptin group; 5—IR + Melatonin + Sitagliptin group; 6—IR + CC group; 7—IR + CC + Melatonin + Sitagliptin group 2 weeks 10 weeks Improving antioxidative and antiapoptotic responses Up-regulation of AMPK/SIRT1 activity via melatonin [ 100 ] Male C57BL/6 J mice 8 weeks T1DM T1DM 50 mg/kg (STZ) by intraperitoneal for 5 consecutive days + intraperitoneal injections of 10 mg/kg/d melatonin for 10 weeks 4 groups 1—normal glucose; 2—high glucose; 3—Mannitol; 4—melatonin 2 weeks 12 weeks after the first injection of STZ amelioration of high glucose-induced CMECs injury by melatonin Treatment of apoptosis and increased AMPK/SIRT1 signaling axis activity by melatonin in CMEC [ 101 ] Adult male Wister rats 8 weeks 170–200 (g) T2DM T2DM nicotinamide (100 mg/kg, ip) 20 min before STZ (55 mg/kg) + melatonin (10 mg/kg) by stomach tube daily for 15 days between 10:0 and 11:00 am N = 20 4 groups (5 rats each) 1—control group received standard diet 2—melatonin treated group 3—diabetic group 4—group receiving melatonin for 15 days after the induction of diabetes 3 days 15 days post diabetic induction of STZ Protective effects of melatonin against hyperglycemia, anti-lipid, antioxidant, anti-inflammatory and anti-apoptotic MLT improves serum glucose levels, HbA1-c, lipid profile, insulin levels and insulin resistance, glutathione and IL-10 and Bcl-2 levels and prevents the increase of pro-inflammatory cytokines and the expression of Bax, caspase-3 and P53 [ 9 ] …”
Section: Resultsmentioning
confidence: 99%
“…Dipeptidyl peptidase-4 inhibitors are among the drugs studied for their potential use for new therapeutic purposes, a strategy referred to as drug repurposing or repositioning [ 9 ]. Recently, a large body of evidence has accumulated showing sitagliptin effectiveness in lessening tissue damage during intestinal [ 24 , 32 ], cardiac [ 23 , 33 ], cerebral [ 30 ], testicular [ 31 ] and renal [ 28 , 29 ] ischemia-reperfusion insult. Likewise, sitagliptin has reduced the histopathological signs of injury and decreased the serum activities of ALT and AST in animal models of hepatic IR [ 21 , 22 , 25 , 26 ], acting via mechanisms employing its anti-inflammatory and antioxidative properties.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have demonstrated pleiotropic properties, including the antioxidative, anti-inflammatory and antiapoptotic action of sitagliptin [ 18 , 19 ], a well-tolerated DPP-4 inhibitor with moderate side effects [ 20 ]. Accordingly, we [ 21 , 22 ], as well as others [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], have shown that sitagliptin alleviates injury caused by IR procedure. However, the molecular background has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%